EIB Investment Report 2021/2022 Recovery as a springboard for change (European Investment Bank, 2022)
The massive resources the European Union is unleashing to rebuild after COVID-19 present a unique opportunity to deal with climate change and improve the ability of firms and individuals to compete in a more digital world. The Investment Report 2021/2022 examines how government interventions helped support investment and enabled firms to weather the crisis. The report's analysis is based on a unique set of databases and data from a survey of 12 500 firms conducted in the summer of 2021.
English
Keywords: Investment and securities; Business & Economics; Investments & Securities